Factors affecting the performance and monitoring of a chlorine wash in preventing Escherichia coli O157:H7 cross-contamination during postharvest washing of cut lettuce. (December 2018) - Fu, Tong-Jen; Li, Yichen; Awad, Deena; Zhou, Ting-Yang; Liu, Lyurui
Abstract: This study examined factors that may affect the performance of a produce wash in preventing E. coli O157:H7 cross-contamination. Fresh-cut romaine lettuce (8 or 20 g) inoculated with ca. 7 log CFU/g of E. coli O157:H7 expressing green fluorescence protein was washed with uninoculated cut lettuce (800 or 2000 g) in 40 L of water for 2 min. Washing trials were performed in both sterile tap water and spent wash water collected from a commercial leafy greens processing facility under different prewash free chlorine levels (0, 5, 20 and 30 ppm), water temperatures (3 and 20 °C), leaf-to-water ratios (1:20 and 1:50), and flow rates (fast, medium, and slow). Performance of the chlorine wash was greatly affected by free chlorine level and wash water quality. Temperature, lettuce-to-water ratio, or water flow rate did not appear to have a significant impact. A prewash free chlorine concentration of 10 or 20 ppm was effective in preventing E. coli O157:H7 cross-contamination when lettuce was washed in tap water in the two washing systems assembled; 30 ppm of chlorine was needed to prevent cross-contamination during washing in industry water. Small-scale (100 ml) inactivation studies were performed to examine the impact of organic and solid contents (with the addition of lettuce juice and play sand) on the antimicrobial efficacy of chlorinated water. Increases in organic matter resulted in greater depletion of chlorine and the presence of solids enabled the pathogen to better survive chlorination; both led to a lower antimicrobial efficacy observed. ORP did not correlate linearly with free chlorine. E. coli O157:H7 cross-contamination was observed when ORP exceeded 650 mV, indicating that a threshold level of 650 mV may not ensure the safety of produce wash water. Since effective chlorine level is highly influenced by wash water quality, monitoring of produce washing systems may best be performed by measuring wash water quality in conjunction with rapid measurement of free chlorine. Highlights: Chlorine level and wash water quality were key parameters affecting performance. Temp, lettuce-to-water ratio, or water flow rate did not have a significant impact. Effective chlorine level to prevent cross-contamination was dependent on water quality. Presence of solids enabled the pathogen to better survive chlorination. Cross-contamination was observed when ORP exceeded the threshold level of 650 mV.